Morbilliviral infections in marine mammals - Seamus, Kennedy (J. Cetacean Res. Manage., 1999)
Epizootics of infectious disease were unknown in cetaceans prior to 1987. However, since then there have been at least three epizootics in dolphins and two in pinniped species. Many of the clinical, pathological and epidemiological features of these events were similar to those of morbilliviral infections in terrestrial mammals. There has been speculation that contaminants may have predisposed marine mammals to these and this is discussed. Morbilliviruses are highly pathogenic viruses and caused epizootics in terrestrial mammals long before the advent of anthropogenic contaminants